2018
DOI: 10.1186/s12936-018-2179-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood parasite infections in a wild population of ravens (Corvus corax) in Bulgaria

Abstract: BackgroundBlood parasites have been studied intensely in many families of avian hosts, but corvids, a particularly cosmopolitan family, remain underexplored. Haemosporidian parasites of the common raven (Corvus corax) have not been studied, although it is the largest, most adaptable, and widespread corvid. Genetic sequence data from parasites of ravens can enhance the understanding of speciation patterns and specificity of haemosporidian parasites in corvids, and shed light how these hosts cope with parasite p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Our current results do not confirm if the adaptations connected with carrion-feeding lifestyle and gut microbiome suppress transmission, or otherwise affect the blood parasite fauna. In conjunction with the patterns found in previous studies on raptor and non-raptor scavengers, it appears probable that habitat features play an important role in the transmission of blood parasites [26,62]. An additional role in the specific features of the host immunity needs to be further explored.…”
Section: Discussionmentioning
confidence: 68%
“…Our current results do not confirm if the adaptations connected with carrion-feeding lifestyle and gut microbiome suppress transmission, or otherwise affect the blood parasite fauna. In conjunction with the patterns found in previous studies on raptor and non-raptor scavengers, it appears probable that habitat features play an important role in the transmission of blood parasites [26,62]. An additional role in the specific features of the host immunity needs to be further explored.…”
Section: Discussionmentioning
confidence: 68%
“…Studies on the prevalence of Leucocytozoon and other haemosporidian parasites in raptors are numerous and mostly suggest high prevalence, in some cases up to 100% ( Jeffries et al, 2015 ; Valkiunas, 2005 ). Recent studies have shown Leucocytozoon infections to be highly prevalent also in passerine species with similar or shorter altricial periods than the studied raptors ( Schmid et al, 2017 ; Schumm et al, 2019 ; Shurulinkov et al, 2018 ). In this study, Leucocytozoon infections were detected in nestlings of all three studied raptor species, as expected from related results ( Bensch et al, 2009 ).…”
Section: Discussionmentioning
confidence: 78%
“…Studies on haemosporidians involving a single host bird species have reported a lower number of lineages in comparison to those found in the cattle egret. A study on the house wren ( Troglodytes aedon ) from the Andes and bordering lowlands revealed 23 distinct lineages [52], while twenty new lineages of haemosporidians were described in a raven ( Corvus corax ) population [15]. The order Ciconiiformes, which includes the cattle egret, had previously been described as having only 33 avian malaria lineages [34].…”
Section: Discussionmentioning
confidence: 99%
“…There are relatively few examples of single-species studies focusing on spatial patterns in the occurrence of haemosporidians [9, 1215]. This approach enables comparing the effects of environmental factors on the prevalence and diversity of haemosporidians.…”
Section: Introductionmentioning
confidence: 99%